2014
DOI: 10.1093/jxb/eru366
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of FLAGELLIN SENSING 2 map to bacterial entry sites in plant shoots and roots

Abstract: SummaryExpression of the flagellin receptor FLS2 is regulated in a cell/tissue-specific and stress-induced manner that correlated with sites of bacterial infection. The vasculature expresses FLS2 and responds to flagellin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
146
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(163 citation statements)
references
References 50 publications
(84 reference statements)
11
146
0
1
Order By: Relevance
“…In contrast to shoots, the control of plant immunity in roots has been largely understudied. Recent work has demonstrated that FLS2 is under different transcriptional control in roots and shoots (Beck et al, 2014). Given the importance of cytokinin for root development and the recent discovery of transcriptional regulation of FLS2 through altered cytokinin levels (Hann et al, 2014), it is possible to suggest that cytokinins may be involved in the control of root immunity, conceivably by regulation of the FLS2 transcript levels in root cells.…”
Section: Cytokinins and The Control Of Meristem Functionmentioning
confidence: 99%
“…In contrast to shoots, the control of plant immunity in roots has been largely understudied. Recent work has demonstrated that FLS2 is under different transcriptional control in roots and shoots (Beck et al, 2014). Given the importance of cytokinin for root development and the recent discovery of transcriptional regulation of FLS2 through altered cytokinin levels (Hann et al, 2014), it is possible to suggest that cytokinins may be involved in the control of root immunity, conceivably by regulation of the FLS2 transcript levels in root cells.…”
Section: Cytokinins and The Control Of Meristem Functionmentioning
confidence: 99%
“…BIR1 may be acting similarly in negatively regulating BAK1 association with primary receptors for PTI. Given the recent data that flg22 treatment leads to a reduction in LR density (Beck et al 2014), the observed defect in bir1-1 LR development, and the suppression of this defect in bak1-5; bir1-1 plants, it is likely that this defect may be caused by inappropriate BAK1-dependent PTI signaling. Further analysis will be necessary to uncover this link.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported previously that bir1-1 mutants display reduced numbers of LRs, but no quantification has been published (Wang et al 2011). In addition, it has been shown recently that treatment of seedlings with the pathogen elicitor peptide flg22 leads to a reduction in overall LR number (Beck et al 2014). To determine the basis of the apparent reduction of mature LRs in bir1-1, 14-dag roots were fixed, cleared, and analyzed microscopically to assess the density of LRP at stages I-VII of development, as well as to characterize the quantity of LRs at the emergence and mature stages.…”
Section: Bir1 Phenotypesmentioning
confidence: 99%
See 2 more Smart Citations